Os tipos de competências organizacionais e suas contribuições para o processo de formação e implementação de estratégias empresariais: estudo de caso no setor de varejo de automóveis - França, Luse Borges (2011)
In the context of the importance of the relationship between strategy and competencies has awakened repercussions mainly in what concerns the effects of this needed interaction developed by two terms. As a means to deepen this topic, the theoretical body presents a structure that goes from the beginning of history, concepts, types, until the approaches relating to variables, as a way to support all levels of discussions that are routed around the problem. As support to substantiate the central point of this research, it is necessary the application of Zarafian model with its competences and the Miles and Snow Typology with the Adaptive cycle and its strategic applications. From these considerations, the goal of this research is to identify, through a case study, the types of organizational skills that contribute to the formation and implementation of business strategies in the automotive retail sector in the city of Juazeiro do Norte-CE. As regards the methodology, the research is exploratory and descriptive character of qualitative nature (semi-structured interview in audio and using content analysis tool that will serve for assessment of data related to skills) and quantitative (application of a questionnaire). The results obtained indicate the preponderance of strategic positions (Defender-40%; oil-36.36%; 18.79%;-analytical and reactive-4.85%), considering them as a reality of extreme and contrary in comparison to those companies that are successful when adopting oil strategies, analytical, advocate and reactive. In relation to the types of skills, the results presented are favorable (process skills, technical skills, competences on organizations, service skills and social skills), but considering the targeting of these features as possibilities in the formation and implementation of organizational strategies as continued practice in organizational success. Based on this argument, and in possession of inferences addressed by literature, company X will need to adopt the kinds of skills (social, on organizations, techniques, services and processes) and strategic positions (oil, analytical, advocate and reactive) that contribute to the achievement of your goals and promote new achievements ahead the competitive market.